Delays, Masks, the Elderly, and Schools: First Covid-19 Wave in the Czech Republic - Berec, Luděk; Smyčka, Jan; Levínský, René; Hromádková, Eva; Šoltés, Michal; Šlerka, Josef; Tuček, Vít; Trnka, Jan; Šmíd, Martin; Zajíček, Milan; Diviák, Tomáš; Neruda, Roman; et al. (Bulletin of mathematical biology, 2022)
Running across the globe for nearly 2 years, the Covid-19 pandemic keeps demonstrating its strength. Despite a lot of understanding, uncertainty regarding the efficiency of interventions still persists. We developed an age-structured epidemic model parameterized with epidemiological and sociological data for the first Covid-19 wave in the Czech Republic and found that (1) starting the spring 2020 lockdown 4 days earlier might prevent half of the confirmed cases by the end of lockdown period, (2) personal protective measures such as face masks appear more effective than just a realized reduction in social contacts, (3) the strategy of sheltering just the elderly is not at all effective, and (4) leaving schools open is a risky strategy. Despite vaccination programs, evidence-based choice and timing of non-pharmaceutical interventions remains an effective weapon against the Covid-19 pandemic.